The Nursing Management of Tourniquet: the infective risk related to its use: Tourniquet management and contamination risk - Paduret, Georgiana; Primosa, Flavia; Bujdos, Mary Jean; Artioli, Giovanna; Sarli, Leopoldo; La Sala, Rachele; Dicembrino, Rita Bruna; Marra, Sandrino Luigi; Marletta, Giuseppe (Acta Biomedica Atenei Parmensis, 2021)
Background and aim of the work: Reusable tourniquets should be considered and used in clinical practice as semi-critical devices, as they are colonized by potentially pathogenic agents, a possible cause of care-related infections. The aim of the study was to analyse the management of tourniquets in the clinical reality of wards, investigating the aspects related to their use in venepuncture procedures, the cleaning process after their use and storage. Methods: It has been conducted an observational study with a questionnaire on a sample of nurses (N = 73) and nursing students (N = 60) recruited in a hospital and in an University of northern Italy. Results: Data revealed a very positive attitude regarding the high standards of hand hygiene among nurses and nursing students sampled; the critical issues concern the lack of shared protocols or guidelines for the management of tourniquets that lead to discussion both on their use in clinical practice and on the disinfection process after use as well as tourniquets disposal. Conclusions: Tourniquets can represent a serious potential danger in terms of infections transmission, especially in the pandemic period we are experiencing; their use is practically transversal in all healthcare settings and it is therefore necessary to implement the use of shared management and disposal guidelines / protocols. From this research it appears that in the setting explored, although much attention is paid to hand hygiene, this aspect still seems to be a critical point of nursing care.